2013
DOI: 10.1038/ncomms3062
|View full text |Cite
|
Sign up to set email alerts
|

PHF20 regulates NF-κB signalling by disrupting recruitment of PP2A to p65

Abstract: Constitutive NF-κB activation in cancer cells is caused by defects in the signalling network responsible for terminating the NF-κB response. Here we report that plant homeodomain finger protein 20 maintains NF-κB in an active state in the nucleus by inhibiting the interaction between PP2A and p65. We show that plant homeodomain finger protein 20 induces canonical NF-κB signalling by increasing the DNA-binding activity of NF-κB subunit p65. In plant homeodomain finger protein 20-overexpressing cells, the termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 45 publications
4
44
0
Order By: Relevance
“…Remarkably, expression of the FBXL11 gene is induced in response to NF-κB activation, forming a unique negative feedback loop similar in effect to the one that involves the well-known negative regulator IκB (5). Recently, the Hur group (20) reported that glioma-expressed antigen 2 (PHF20) interacts with p65 by recognizing methylation at K218 and K221. This methylation-dependent interaction of PHF20 with p65 leads to persistent NF-κB phosphorylation and function by limiting the recruitment of protein phosphatase PP2A to p65 (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, expression of the FBXL11 gene is induced in response to NF-κB activation, forming a unique negative feedback loop similar in effect to the one that involves the well-known negative regulator IκB (5). Recently, the Hur group (20) reported that glioma-expressed antigen 2 (PHF20) interacts with p65 by recognizing methylation at K218 and K221. This methylation-dependent interaction of PHF20 with p65 leads to persistent NF-κB phosphorylation and function by limiting the recruitment of protein phosphatase PP2A to p65 (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Hur group (20) reported that glioma-expressed antigen 2 (PHF20) interacts with p65 by recognizing methylation at K218 and K221. This methylation-dependent interaction of PHF20 with p65 leads to persistent NF-κB phosphorylation and function by limiting the recruitment of protein phosphatase PP2A to p65 (20). Yang et al (6) reported that K314 and K315 of p65 are monomethylated by SET7/9 in response to NF-κB activation, an inhibitory modification that stimulates proteosome-mediated degradation of promoter-associated p65.…”
Section: Discussionmentioning
confidence: 99%
“…The activating monomethylation of K218 and di-methylation of K221 are both catalyzed by the H3K36 methyltransferase nuclear receptorbinding SET domain-containing protein (NSD1) and the methyl groups can be removed, leading to loss of NF-κB function, by the H3K36 demethylase FBXL11. Recently, the Hur group (16) reported that glioma-expressed antigen 2 (PHF20) interacts with p65 by recognizing methylation at K218 and K221. This methylation-dependent interaction of PHF20 with p65 leads to persistent NF-κB phosphorylation and function by limiting the recruitment of protein phosphatase PP2A to p65 (16).…”
mentioning
confidence: 99%
“…Recently, the Hur group (16) reported that glioma-expressed antigen 2 (PHF20) interacts with p65 by recognizing methylation at K218 and K221. This methylation-dependent interaction of PHF20 with p65 leads to persistent NF-κB phosphorylation and function by limiting the recruitment of protein phosphatase PP2A to p65 (16). This important observation further confirms the biological importance of lysine methylation of p65.…”
mentioning
confidence: 99%
“…The methylation of p65 blocks recruitment of PP2A to p65, thereby leading to the persistent phosphorylation of p65 [34]. By using the immunohistochemistry (IHC) staining method, the authors showed that PHF20 and phosphorylated p65 are localized in the nucleus in glioma tissue specimens.…”
Section: Lysine Methylation Of P65mentioning
confidence: 99%